Artisanal gill-net fishery catches of the catfish, Schilbe intermedius (Teleostei: Schilbeidae) in two tributaries of Ouémé river, Bénin, West Africa. - LALEYE, PHILIPPE A. (My University, 2005)
Artisanal fishery gill-net catches of the catfish Schilbe intermedius were studied in the Okpara and Zou tributaries of the Ouémé River, Benin in 1999 and 2000. The largest fish caught at the Toué and Kpassa stations measured 26.2cm and 24.5cm (TL) respectively. The success of artisanal fishing for schilbeids varied during the day, with the highest fish catches being recorded at approximately 22h00 and at 07h00 and the lowest between 13h15 and 16h15. The monthly production at Kpassa varied between 9.0g and 900.0g (average 206.3g) and between 3.3g and 17 320g (average 2 603.4g) at Toué. The monthly production fluctuated considerably. At the two stations, fewer fish were caught each month in the second year than in the same months in the first year. Nets of between 10 and 15mm stretch mesh were the most efficient. Above 15mm, gill-net fishing became less effective. Large fish were often taken with gill-nets of 20–30mm stretch mesh. Beyond these mesh sizes, the gill-net yield and catch decreased.
Keywords: gill-net fisheries; Okpara and Zou tributaries; Ouémé River; Schilbe intermedius